2020
DOI: 10.1111/are.15000
|View full text |Cite
|
Sign up to set email alerts
|

Dietary essential oil extract from sweet orange (Citrus sinensis) and bitter lemon (Citrus limon) peels improved Nile tilapia performance and health status

Abstract: The effects of dietary essential oils extract from sweet orange (Citrus sinensis) (OEO) and/or lemon (Citrus limon) (LEO) peels on performance and health status of Nile tilapia were investigated. Seven triplicate groups (Control "CG", OEO1‰, OEO3‰, LEO0.75‰, LEO1‰, OEO1‰ × LEO0.75‰ and OEO3‰ × LEO1‰) of fish (16.42 ± 0.059 g, N = 210) were fed basal diet, basal diet contain OEO 1‰, OEO 3‰, LEO 0.75‰, LEO 1‰, OEO 1‰ × LEO 0.75‰ and OEO 3‰ × LEO1‰ respectively, for 60 day. Results showed significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 64 publications
2
32
0
1
Order By: Relevance
“…Similar results were observed by Mohamed et al (2020) andChoi et al (2014). Therefore, it could be suggested that dietary UFME might stimulate the somatotrophic axis as demonstrated by the upregulation of ILGF-1 and GH.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were observed by Mohamed et al (2020) andChoi et al (2014). Therefore, it could be suggested that dietary UFME might stimulate the somatotrophic axis as demonstrated by the upregulation of ILGF-1 and GH.…”
Section: Discussionsupporting
confidence: 79%
“…PA was increased fish fed with DEO, nonetheless only significantly different in the DEO-2 group when compared to the control group (P<0.05). According to recent studies, PA was increased when essential oils were used in the diets, such as sweet orange and lemon peels essential oils in Nile tilapia (Mohamed et al, 2020), oregano essential oil in common carp (Abdel-Latif et al, 2020), thyme essential oil in African catfish (Euony et al, 2020), orange peels essential oil in rainbow trout (Gültepe, 2020). RBA is an indicator of innate immunity and manifests as high oxygen consumption during phagocytosis (Biller-Takahashi et al, 2013;Biller and Takahashi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Palm kernel oil researches are carried out in terms of fatty acid content, energy level, vitamin E content, carotenoids, cost-effectiveness, and its use is increasing day by day especially in Far Eastern countries (Turchini et al, 2010). It is known that essential oils are effectively contributing to the growth performance of fish as well as against fish diseases due to their antimicrobial, antioxidant properties, and secondary metabolites (Mohamed et al, 2020). Any studies on the effects and/or usage of date kernel essential oil were not found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Latency to start feeding was recorded and defined as the time in seconds elapsed between the provision of feed on the aquarium water and the first fish starting to eat. Feeding duration was also recorded and described as the time in minutes elapsed between the first fish starting to eat until the last fish ending feed consumption (Abdel‐Hay et al., 2019; Mohamed et al., 2020).…”
Section: Methodsmentioning
confidence: 99%